Cervical Spine Involvement in Rheumatoid Arthritis: Case Report - Ali Aydeniz; Özlem Altındağ; Savaş Gürsoy (Archives of Rheumatology, 2009)
Cervical spine involvement occurs in over half of the patients with rheumatoid arthritis. The destruction of the spine ranges from minimal subluxation to atlantoaxial dislocation and compression of the spinal cord and brainstem, and hence may result in sudden death. In this paper, we present a case of seronegative rheumatoid arthritis with cervical involvement, and we review cervical involvement in view of the related literature. (Turk J Rheumatol 2009; 24: 222-4)